Deconstruction of leadership accountability of neoliberalist universities based on Ki Hajar dewantara's trilogy leadership - Rahman, Arief; Djamhuri, Ali (The International Journal of Accounting and Business Society, 2024)
Purpose: This study aims to deconstruct the concept of university leadership accountability, which is often influenced by neoliberal values, by applying Ki Hajar Dewantara's philosophical framework. Method: The study employs a deconstructive approach, utilizing three operating modes: description, analysis, and transformation. This involves describing the current reality of neoliberal leadership accountability, analyzing its explicit and implicit meanings, and finally, transforming the concept to align with the values espoused by Ki Hajar Dewantara. Findings: The deconstruction process reveals a concept of leadership accountability that emphasizes moral, spiritual, and sincere compassion. This approach reflects the spirit of Ki Hajar Dewantara's "Ing Ngarsa Sung Tuladha" (leading by example), "Ing Madya Mangun Karsa" (inspiring and empowering others), and "Tut Wuri Handayani" (supporting and guiding from behind). This approach emphasizes that learning leadership accountability involves not only cognitive understanding but also the cultivation of moral character, emotional intelligence, and sincere intentions. Practical Implications: This study's findings can inform the development of more ethical and humane leadership practices in higher education. By integrating moral, spiritual, and sincere values into the concept of leadership accountability, universities can foster a more just and equitable environment for students, faculty, and staff. Originality: This study contributes to the existing literature by: 1) applying Ki Hajar Dewantara's philosophy to deconstruct the concept of leadership accountability in higher education, 2) offering a critical analysis of the influence of neoliberal values on leadership practices; and 3) proposing a transformative framework for leadership accountability that emphasizes moral, spiritual, and compassionate values. Paper Type: This research can be categorized as a philosophical or theoretical study within the field of higher education leadership and management. Keywords: Leadership Accountability, Deconstruction, Ki Hajar Philosophy.